(untitled) (Plant Tissue Culture and Biotechnology, 2010)
A protocol was established for mass propagation of the valuable medicinal plant Ficus religiosa L. (Moraceae) through in vitro culture using apical and axillary buds of young sprouts from selected plants. Best shoot induction was observed on MS basal medium supplemented with 0.5 mg/l BAP + 0.1 mg/l IAA, in which 78 per cent of the explants produced 16 shoots per culture. Repeated subcultures in the same medium, resulted rapid shoot multiplication with 24 shoots per culture. In vitro raised shoots rooted on half strength MS supplemented with 2.0 mg/l IBA + 0.1 mg/l NAA. For acclimatization and transplantation, the plantlets in the rooting culture tubes were kept in normal room temperature for seven days before transplanting in pots where plantlets were reared for three weeks. The survival rate of regenerated plantlets was 85 per cent. Key words: Ficus religiosa, Medicinal plant, Shoot proliferation, Regeneration, Acclimatization D.O.I. 10.3329/ptcb.v19i1.4987 Plant Tissue Cult. & Biotech. 19(1): 71-78, 2009 (June)